2021
DOI: 10.1002/path.5753
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenous presence of neutrophil extracellular traps in human solid tumours is partially dependent on IL‐8

Abstract: Myers-Squibb, Agenus and Torque Therapeutics. All other authors declared no conflicts of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 51 publications
2
64
0
Order By: Relevance
“…Since NET formation also primed the premetastatic niche and promoted tumor dissemination in a lung metastasis model of breast cancer (41), inhibition of NET hampered the progression of established tumors and impaired metastasis (40). Concordantly, an increased NET area was detected in relapsed breast cancer specimens in our cohort (42). Thus, we could anticipate that several NET inhibitors currently tested in the clinic including PAD4 antagonists, IL-8 neutralizing antibodies (43), and CXCR2 inhibitors could also impact LRF.…”
Section: Clinical Relevance Of Enpp1 and Net In Lrfsupporting
confidence: 61%
See 1 more Smart Citation
“…Since NET formation also primed the premetastatic niche and promoted tumor dissemination in a lung metastasis model of breast cancer (41), inhibition of NET hampered the progression of established tumors and impaired metastasis (40). Concordantly, an increased NET area was detected in relapsed breast cancer specimens in our cohort (42). Thus, we could anticipate that several NET inhibitors currently tested in the clinic including PAD4 antagonists, IL-8 neutralizing antibodies (43), and CXCR2 inhibitors could also impact LRF.…”
Section: Clinical Relevance Of Enpp1 and Net In Lrfsupporting
confidence: 61%
“…Software, an open-source Java-based image processing software. Measurement workflow and scoring have been previously described (42). In short, neutrophils were identified by the co-staining with CD15 and MPO.…”
Section: And Imagejmentioning
confidence: 99%
“…A further study demonstrated that CXCL8 induced tumor-associated neutrophil and granulocytic MDSC extrusion of NETs, which shield tumor cells from contact with CD8 + T cells and limit the anti-PD-1 immune response to cancer [ 98 ]. Conclusive evidence showed that multiple human cancer types contain NETs, which had a positive association with CXCL8 and reduced CD8 + T-cell infiltration [ 99 ]. Tumorous CXCL8 mediates increased NETs formation in the TME, promoting colorectal cancer liver metastasis [ 100 ].…”
Section: Cxcl8-cxcr1/2 Signaling Pathwaymentioning
confidence: 99%
“…IL-8 is increased in breast cancer tissues compared to adjacent normal breast tissues [ 31 ]. IL-8 secreted from tumors promotes the release of NETs [ 32 , 33 ]. Furthermore, IL-8 is positively correlated with NETs in non-small cell lung cancer (NSCLC) and melanoma [ 32 ].…”
Section: Molecular Pathway Of Netosis Stimulated By Various Agonistsmentioning
confidence: 99%
“…IL-8 secreted from tumors promotes the release of NETs [ 32 , 33 ]. Furthermore, IL-8 is positively correlated with NETs in non-small cell lung cancer (NSCLC) and melanoma [ 32 ]. IL-8 can easily bind with C-X-C motif chemokine receptor 1 (CXCR1) and C-X-C motif chemokine receptor 2 (CXCR2) [ 34 ].…”
Section: Molecular Pathway Of Netosis Stimulated By Various Agonistsmentioning
confidence: 99%